Motif of Death in Irina Odoyevtseva’s Prose - Witczak, Patryk (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
The present paper brings an analysis of the motif of death in Irina Odoyevtseva’s novels Zerkalo, Izolda and Angel smerti. In the prose of Odoyevtseva, who belonged to the younger generation of the Russian Emigration (the first wave), death is a frequent motif. The author explores how Odoyevtseva refers to Mikhail Lermontov’s poems and to the Celtic story of Tristan and Iseult.